2021
DOI: 10.3390/polym13193303
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of Electrostatic Filtration Efficiency and Antibacterial Efficacy of Antibacterial Electret Polypropylene Filters: Effects of Using Low Molecular Antibacterial Agent as Additive

Abstract: In recent years, air filtration has been gaining much attention, and now people are much more concerned about antibacterial filters due to the spreading of COVID-19. The electret polypropylene (PP) nonwoven fabrics possess excellent filtration efficiency but a limited antibacterial effect against S. aureus and E. coli, and therefore triclosan is used in this study. Serving as an antibacterial agent, triclosan with a low molecular weight is an effective additive for the test results, indicating that the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Although nanofiber filters exhibit exceptional efficiency, they have a common problem of high air resistance . Some studies enhanced filter media with additional electrostatic force to reduce air resistance. , Choi et al fabricated a polyethylene terephthalate (PET)/Al filter and used an ionizer to charge the polluted inlet air, showing high capture efficiency of ∼99.99% and high antimicrobial activity of ∼94.8 and ∼96.9% against airborne E. coli and S.…”
Section: Introductionmentioning
confidence: 99%
“…Although nanofiber filters exhibit exceptional efficiency, they have a common problem of high air resistance . Some studies enhanced filter media with additional electrostatic force to reduce air resistance. , Choi et al fabricated a polyethylene terephthalate (PET)/Al filter and used an ionizer to charge the polluted inlet air, showing high capture efficiency of ∼99.99% and high antimicrobial activity of ∼94.8 and ∼96.9% against airborne E. coli and S.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the assessment of bacteriostasis confirmed that the surface of the wrap-coated non-woven fabric had good surface bacteriostasis against E. coli, C. albicans , and S. aureus due to the dual effects of chemical stability of the fluoroacrylic copolymer coating and nano-protrusion morphology (Table S7, ESI†). 7…”
mentioning
confidence: 99%